Pengaruh Literasi Keuangan Syariah terhadap Keputusan Nasabah dalam Memilih Cicilan Kendaraan Islami - Harandra Anugrah Yusuf; Madian Muhammad Muchlis (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to analyze the influence of Islamic financial literacy on customer decisions in choosing Islamic vehicle installments in Indonesia. Using a quantitative approach, a survey was conducted on several respondents in five major cities in Indonesia. The results showed that the level of Islamic financial literacy has a significant positive influence on customer preferences for choosing Islamic vehicle installments. Logistic regression analysis revealed that every one-point increase in the Islamic financial literacy score increases the odds of choosing Islamic vehicle installments by 4.9%. Demographic factors such as age, education, and income also have a significant influence. These findings highlight the importance of efforts to improve Islamic financial literacy as a strategy to encourage the adoption of Islamic financing products. Practical implications include the need for targeted education programs, improved product communication, and innovation in the development of competitive Islamic financing products.